Flexural Capacity Of Ultra-High Performance Fibre Reinforced Concrete (Uhpfrc) Rectangular Beam - Cheah, Zu Yi (Universiti Sains Malaysia, 2018)
This study was done to identify the optimum fibre content to achieve maximum flexural capacity of ultra-high performance fibre-reinforced concrete (UHPFRC) beam. Smooth micro steel fibres of diameter 0.2 mm and length 20 mm were used in the mix which was proposed by Tayeh et al. (2013). Four batches of concrete were prepared with fibre content of 0%, 0.8%, 1.6% and 2.4% by mass, replacing the quartz sand. The targeted designed compressive strength is from 100 MPa to 120 MPa. A total of 5 tests were conducted on the concrete samples as in accordance to BS1881. They are flow table test, cube and cylinder compression test, tensile splitting test and four-point flexural test. Four beams of size 100 mm × 300 mm × 2000 mm were cast for the four point flexural test. Based on the results, the super-plasticizer (SP) needed for 0.8%, 1.6% and 2.4% UHPFRC to achieve flow of 600 mm is 1.36%, 1.25% and 1.14% by mass respectively. Less SP is required to achieve the same fresh concrete flow when the fibre content increases. Addition of fibre increases the compressive strength of UHPC. The optimum fibre content to achieve maximum compressive strength (116.8 MPa, 22.6% higher than UHPC) is 0.8% by mass. Besides that, adding steel fibre increases the tensile splitting strength of UHPC too. Maximum tensile splitting strength (75.3 MPa) is achieved at 1.6% fibre content with the increment of 35.2%. Meanwhile, maximum flexural strength (10.24 MPa) was achieved at 1.6% fibre content too, with the increment of 24.4% as compared to UHPC. Further increment in fibre content shows adverse effect on the beam flexural strength. Minor balling effect took place when 2.4% of fibre mass is used. Lastly, micro steel fibre is found to improve the ductility of UHPC, enhancing the crack control.